The effects of customer justice perception and affect on customer citizenship behavior and customer dysfunctional behavior - Yi, Youjae; Gong, Taeshik (Industrial marketing management, 2008)
This research investigates whether customer justice perception influences affect and, in turn, customer citizenship behavior and customer dysfunctional behavior. Drawing on the social exchange theory and frustration–aggression theory, this paper argues that distributive justice, procedural justice, and interactional justice influence positive affect as well as negative affect. Furthermore, this study argues that positive affect influences customer citizenship behavior, while negative affect influences customer dysfunctional behavior. To test these relationships, the present study uses data from 209 executive-MBA students and 68 buyer companies. The results of the structural equation analysis reveal that most of these hypotheses are supported. Following a discussion of the results, research limitations and directions for future research are offered.